Genetic variants in 5′UTR and exonic region of NPY gene alter the reproduction performance in Indian cattle breeds. Issue 2 (1st November 2022) - Singh, Umesh; Alex, Rani; Chaudhary, Ayushi; Deb, Rajib; Raja, Thiruvothur Venketesan; Rathod, Bharatsingh; Savaliya, Bhagavanji Dayabhai; Kumar, Sushil; Das, Achintya Kumar
Abstract: Neuropeptide Y (NPY) is one of the most potent orexigenic factors which can produce diverse effects on behaviour and other physiological functions and is highly conserved in evolution. The present study was aimed to identify and associate SNPs in the 5′ UTR and exon2 region of the NPY gene with reproduction and production traits in Kankrej cattle of Indian origin. Three mutations in the 5′‐UTR region and one mutation in the exon2 region of the NPY gene were identified by PCR‐SSCP and PCR‐RFLP, respectively, followed by sequencing. Further, association studies were conducted with reproduction and production traits in Kankrej cattle. The GACCGA genotyped animals based on the 5′UTR variants indicated better dry period and calving interval, whereas with GGCCGG genotypes showed higher total lactation milk yield and 305‐day milk yield in comparison to other genotypes. Also, service period and inter calving period varied significantly among the genotypes of exon2, as the GG genotyped animals had significantly longer calving interval. Other traits like age at first heat, age at first service and age at first calving were not affected by the mutations. So, the present study outlined that the bovine NPY gene may be considered to be one of the candidate gene for improvement of reproductive performance of cattle, after validation on large sample size.